2018
DOI: 10.1016/j.nicl.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Gray-matter-specific MR imaging improves the detection of epileptogenic zones in focal cortical dysplasia: A new sequence called fluid and white matter suppression (FLAWS)

Abstract: ObjectivesTo evaluate the diagnostic value and characteristic features of FCD epileptogenic zones using a novel sequence called fluid and white matter suppression (FLAWS).Materials and methodsThirty-nine patients with pathologically confirmed FCD and good surgery outcomes (class I or II, according to the Engel Epilepsy Surgery Outcome Scale) were retrospectively included in the study. All the patients underwent a preoperative whole-brain MRI examination that included conventional sequences (T2WI, T1WI, two-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…This MP2RAGE can be a suitable sequence to delineate the lesion with high gray-white matter contrast, such as FCD [60]. A new sequence called fluid and white matter suppression (FLAWS) has been reported to be useful for the detection of FCD EZs [61]. FLAWS sequence acquires two images of 3D high spatial resolution images with white-matter signal suppression and cerebrospinal fluid (CSF) signal suppression.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This MP2RAGE can be a suitable sequence to delineate the lesion with high gray-white matter contrast, such as FCD [60]. A new sequence called fluid and white matter suppression (FLAWS) has been reported to be useful for the detection of FCD EZs [61]. FLAWS sequence acquires two images of 3D high spatial resolution images with white-matter signal suppression and cerebrospinal fluid (CSF) signal suppression.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This GM‐specific contrast is similar in purpose to the T 2 ‐weighted double‐inversion recovery contrast, 11 which is used to detect WM and intracortical lesions in multiple sclerosis 12 . These FLAWS properties suggest that this sequence has potential for the detection and segmentation of brain lesions 8,13,14 . The FLAWS sequence has also been shown to be of interest to visualize basal ganglia structures 15,16 and to perform brain tissue segmentation 17 …”
Section: Introductionmentioning
confidence: 97%
“…12 These FLAWS properties suggest that this sequence has potential for the detection and segmentation of brain lesions. 8,13,14 The FLAWS sequence has also been shown to be of interest to visualize basal ganglia structures 15,16 and to perform brain tissue segmentation. 17 Despite the potential clinical interest provided by the FLAWS sequence, its use has been limited for 7T imaging as it could not provide a bias-reduced T 1 -weighted image and its associated T 1 map.…”
Section: Introductionmentioning
confidence: 99%
“…However, reports of FLAWS in epilepsy are rare because of its novelty. In a pilot study, we found that FLAWS was superior to conventional MRI sequences [T1, T2, and fluid-attenuated inversion recovery (FLAIR)] in visually identifying epileptic lesions among patients with both MRI-positive and MRI-negative focal cortical dysplasia (FCD) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%